The effects of drive level errors on optical SSB system performance - Abdul Rashid, Hairul Azhar; Chuah, Hean Teik; Tayahi, Moncef B.; Al-Qdah, Malik T.; Lee, Ruen Chung (The Institute of Electronics, Information and Communication Engineers, 2006)
This paper presents a system performance analysis of an optical single sideband system (OSSB) when drive level errors occur in the modulating signal driving the dual arm Mach-Zehnder modulator (MZM). The performance is evaluated in terms of the optical sideband suppression, frequency response and power penalty measurements. Experiments are carried out and a mathematical model of the OSSB system incorporating the drive level error is developed. The theoretical and experimental results suggest that the drive level error leads to reduced system performance as a result of poor received subcarrier power. The overall frequency response of the system, which is affected by drive level errors, accumulated CD and subcarrier frequency, has a direct influence over the power penalty. However, reduction in power penalty slope is observed at peaks of the OSSB frequency response.